Evaluating the Role of CBC-Derived Indices in Children with Hashimoto’s Thyroiditis - Andrei-Ioan Munteanu; Iulius Jugănaru; Delia-Maria Nicoară; Niculina Mang; Raluca Vasilescu; Giorgiana-Flavia Brad; Alexandra-Cristina Scutca; Raluca Asproniu; Lucian-Ioan Cristun; Otilia Mărginean (Diagnostics)
Background/Objectives: Hashimoto’s thyroiditis (HT) is an autoimmune disorder characterized by chronic inflammation of the thyroid gland. Recent evidence indicates that the inflammation may extend beyond the thyroid. The study aims to explore the potential of complete blood count (CBC)-derived indices as markers of systemic inflammation in HT. Materials and Methods: This cross-sectional retrospective study from 1 January 2015, to 31 December 2023 included 147 pediatric HT patients and 144 apparently healthy controls. Thyroid profiles, antibodies, CBC, and protein electrophoresis data were collected from patient records. CBC-derived indices were calculated and compared between the HT and control groups, as well as among HT subgroups. Results: The median age of HT patients was 13.6 years (range: 11.2–15.5 years), with 66% being girls. The control group had a similar age and gender distribution, with a median age of 13.7 years (range: 11–15.8 years) and 70.8% girls. Of the HT patients, 50% had subclinical HT, 15% were euthyroid, and 34% had overt thyroid dysfunction. HT patients showed significantly higher neutrophil and lymphocyte counts, as well as all evaluated CBC-derived indices than controls (p < 0.001)). These differences were not significant among HT subgroups. Logistic regression indicated a strong association between an elevated neutrophil-to-lymphocyte ratio (NLR) and HT diagnosis (p < 0.001), while ROC analysis confirmed NLR as the most accurate CBC-derived marker for distinguishing HT from controls. Conclusions: Elevated NLR levels in pediatric HT patients provide additional evidence that inflammation may extend beyond the thyroid gland. These results support the potential of NLR as a reliable and accessible biomarker for evaluating inflammation in Hashimoto’s thyroiditis.